Peran Keterbukaan Komunikasi dalam Membangun Budaya Organisasi Untuk Meningkatkan Citra Diri Kepolisian - Intan Fadilah Nasution; Salwa Azzahrah; Eka Resmawati; Aura Islamyazizah; Tugimin Supriyadi (Observasi : Jurnal Publikasi Ilmu Psikologi, 2024)
Communication in organisational culture is a very important element that affects various aspects of organisational operations and effectiveness. Organisational culture encompasses the values, beliefs and norms held in common by members of the organisation, and communication is the primary means of spreading and maintaining that culture. A strong and positive organisational culture is essential for police institutions to improve their image in the eyes of the public. This organisational culture includes the values, beliefs, behaviours and norms shared by all members of the police force. Police self-image is the perception and judgement that the public has of the police institution. This image is very important as it affects the level of trust, support and co-operation between the police and the community. To improve self-image, the police need to implement a comprehensive and sustainable approach. Through transparency, professionalism, community involvement, effective communication, appropriate conflict handling, innovation, training, rewards, and good media management, the police can build and maintain a positive image in the eyes of the community. A good image not only increases community trust and support but also strengthens the police force's ability to perform their duties effectively. Organisational Culture Communication is the study of how an organisation's culture affects communication within it. Whereas police self-image is concerned with the perceptions and identities that police officers and the public have of the police institution. This study examines how communication within the police organisation affects the self-image of police officers and how that self-image affects the relationship between the police and the Community.